2021
DOI: 10.3389/fevo.2021.706887
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Changes in Hot Spring Frog Tadpoles (Buergeria otai) in Response to Heat Stress

Abstract: Buergeria frog tadpoles exhibit high thermal tolerance and are occasionally found in water pools that temporarily exceed 40°C. With the aim of understanding how they can cope with the severe heat stress, we performed RNA-seq of three heat-treated (38°C) and three control (25°C) tadpoles and compared their transcriptomic profiles. We identified 382 differentially expressed transcripts. A protein-protein interaction (PPI) network analysis of these transcripts further identified hub proteins involved in protein d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The reverse transcription reaction was performed with extracted total RNA as a template and oligo-dT primers to synthesize complementary DNA using the ReverTra Ace® (Toyobo, Osaka, Japan), according to the manufacturer’s instructions. The PCR primers were designed according to the nucleotide sequences of TRPV1 or TRPA1 of B. japonica obtained by RNA sequencing analysis ( Komaki et al 2021 ). For TRPV1, the first round of PCR was performed using the reverse-transcribed products as the template with forward (5′-CATCAGAAGGAATCATTTTAAGACTAGC-3′) and reverse (5′-TGTTTGTTATCCAACTTACCAGTGTC-3′) primers.…”
Section: Methodsmentioning
confidence: 99%
“…The reverse transcription reaction was performed with extracted total RNA as a template and oligo-dT primers to synthesize complementary DNA using the ReverTra Ace® (Toyobo, Osaka, Japan), according to the manufacturer’s instructions. The PCR primers were designed according to the nucleotide sequences of TRPV1 or TRPA1 of B. japonica obtained by RNA sequencing analysis ( Komaki et al 2021 ). For TRPV1, the first round of PCR was performed using the reverse-transcribed products as the template with forward (5′-CATCAGAAGGAATCATTTTAAGACTAGC-3′) and reverse (5′-TGTTTGTTATCCAACTTACCAGTGTC-3′) primers.…”
Section: Methodsmentioning
confidence: 99%
“…These are unexpected results. HSP genes were likewise downregulated in E. tynerensis (Oklahoma salamander) [ 35 ] and B. otai tadpoles [ 23 ], but upregulated in Quasipaa spinosa [ 64 ] under heat stress. Heat shock proteins are induced by a variety of stressors, despite their name referring to their reaction to heat stress.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative transcriptome analysis of three acclimatized groups of Quasipaa boulengeri tadpoles found key differentially expressed genes which coincided with phenotype and hormone level and offered a suitable rearing temperature [ 22 ]. Transcriptomic profiles and protein-protein interaction analysis of heat-treated Buergeria otai tadpoles exhibit global suppression of DNA transcription and mRNA translation that ensure them to survive high temperatures [ 23 ]. Similarly, through transcriptome analysis, it was found that genes involved in secretion and defensive function are highly expressed in the skin of Rana chensinensis [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation